On Saturday, March 8, 2014 8:46:21 PM UTC-6, Chris Angelico wrote:
# As above, start here
a = b
# Multiply both sides by a
aa = ba
# Subtract bb (aka b squared, ASCII-friendly) from both sides
aa - bb = ba - bb
# Factor (both sides separately)
(a + b) (a - b) = b (a - b)        <========of course all you really proved is that  zero == zero
# Cancel out the multiplication by (a - b)
a + b = b
# Subtract b from both sides
a = 0 

But then again, it really is a straw man (on steroids) because nobody is really surprised by
the absurdity

   postulate:  a=b
   conclusion:  a=0

At least no one should be surprised by an absurdity.  On the other hand once they  see
the proof run by them, um, quickly--- slight of hand, as it were, they might be surprised
if they don't catch it right away. 

{still laughing}

love it